Environmental nursing practices as a solution for reducing exposure to environmental hazards - Nurhadijah, Sitti; Zamaa, Muhammad Sahlan; Harun, Basmalah; Sahida, Muti; Wahyuni, Andi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This literature review investigates nursing interventions aimed at reducing exposure to environmental hazards. Environmental hazards, such as chemical exposure, pollution, and toxins, have significant adverse effects on both human health and ecosystems, necessitating effective intervention strategies. Method: A systematic review was conducted by searching three major databases—PubMed, Scopus, and ISI Web of Knowledge—using specific keywords related to environmental hazards, settings, health impacts, and nursing interventions. It synthesizes findings from studies published between 2020 and 2025, focusing on environmental health, exposure prevention, risk assessment, and health education. The selection of papers adhered to the PRISMA guidelines to ensure comprehensive coverage of relevant literature. Results: The review highlights the widespread impact of environmental hazards, including pollutants like PFAS, pesticides, and microplastics, which contribute to health issues such as respiratory diseases, developmental disorders, and cancer. Additionally, studies reveal the importance of environmental nursing in managing these risks, with interventions such as admission screenings for infections like Candida auris and the integration of experiential learning in health curricula to enhance community health education. Community health nursing and health education play pivotal roles in promoting awareness and preventing diseases by targeting social and environmental determinants of health. Conclusion: This review underscores the importance of multi-faceted nursing interventions in addressing environmental health risks. Findings demonstrate the critical role of nurses in both direct healthcare and community education efforts to mitigate environmental hazards. Moving forward, comprehensive risk assessment and community-based approaches should be prioritized to reduce health disparities and enhance public health outcomes. Novelty/Originality of this article: The implications of this research suggest that enhancing nursing education on environmental health and integrating evidence-based interventions into healthcare practices will be crucial for effective mitigation of environmental risks and promotion of long-term health improvements.